2018
DOI: 10.1088/1361-6455/aa9784
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of resonant auger effect with chirped x-ray free-electron laser pulse

Abstract: We study the Auger effect induced by strong x-ray free-electron lasers (XFELs) propagating through the resonant argon vapors through solving the Maxwell-Bloch equations numerically. The simulations are based on the three-level system with the carrier frequency tuned in the 2p3/2-4s resonance. It is shown that the Auger branching is sentive to the pulse area and duration. The relative Auger yield can be suppressed in the course of pulse propagation due to the interplay between the Auger decay and stimulated emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 30 publications
(44 reference statements)
0
7
2
Order By: Relevance
“…However, along with gaining a basic understanding of a process it is always important to devise schemes to control the outcome of a process so that it can be put to significant uses. Recently schemes have been proposed where x-ray/x-uv attosecond laser sources are chirped to investigate different field induced processes like ionization [23,24], stimulated resonant inelastic scattering [25], RA [26] etc. One such recent work has reported that chirping of a free electron laser can induce suppression of the RA process in the course of pulse propagation [26].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, along with gaining a basic understanding of a process it is always important to devise schemes to control the outcome of a process so that it can be put to significant uses. Recently schemes have been proposed where x-ray/x-uv attosecond laser sources are chirped to investigate different field induced processes like ionization [23,24], stimulated resonant inelastic scattering [25], RA [26] etc. One such recent work has reported that chirping of a free electron laser can induce suppression of the RA process in the course of pulse propagation [26].…”
Section: Introductionmentioning
confidence: 99%
“…Recently schemes have been proposed where x-ray/x-uv attosecond laser sources are chirped to investigate different field induced processes like ionization [23,24], stimulated resonant inelastic scattering [25], RA [26] etc. One such recent work has reported that chirping of a free electron laser can induce suppression of the RA process in the course of pulse propagation [26]. The simulations involving the solution of the Maxwell-Bloch equations consider a three level model where RA decay takes place from a single core-excited state.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At these intensities, X-ray matter interaction becomes nonlinear creating room for studies of nonlinear effects like stimulated X-ray Raman scattering [3-5, [8][9][10], pulse compression [3-5], X-ray four-wave mixing [3-5, 11, 12], and nonlinear wave mixing of X-ray and near-infrared beams [13]. Special attention was paid to the competition between stimulated X-ray emission and Auger decay [14][15][16]. Second harmonic generation (SHG) is a nonlinear optical process of sum frequency generation which produces new photons with twice the frequency.…”
Section: Introductionmentioning
confidence: 99%